Clinicopathologic Assay of 15 Tumor Resections in a Family with Neurofibromatosis Type 2 - Di Maio, Salvatore; Mrak, Goran; Juric-Sekhar, Gordana; Born, Donald; Mantovani, Alessandra; Sekhar, Laligam N. (Journal of Neurological Surgery Part B: Skull Base, 2012)
The objective of this study is the management of multiple family members with multiple neurofibromatosis type 2 (NF2) related tumors of the skull base that can be challenging, on purely technical, decision-making, and ethical levels. These issues are addressed in this manuscript based on an experience treating an unique large family with NF2. A retrospective chart review was performed, reviewing clinical, radiological, surgical, and pathological data. A unique family of 17 siblings, whose father was the proband as a sporadic mutation is reported. Over a 4-month period, five of eight affected siblings underwent 12 procedures for resection of 15 different NF2-related tumors. This single family experience of NF2-related skull base tumors underscores the importance of preservation of function and quality of life as the major determinants of treatment success.
Keywords: neurofibromatosis type 2; NF2 associated tumors; vestibular schwannoma; meningioma; quality of life; ethics